2007
DOI: 10.1152/ajprenal.00335.2006
|View full text |Cite
|
Sign up to set email alerts
|

WNK4 kinase is a negative regulator of K+-Clcotransporters

Abstract: WNK kinases [with no lysine (K) kinase] are emerging as regulators of several membrane transport proteins in which WNKs act as molecular switches that coordinate the activity of several players. Members of the cation-coupled chloride cotransporters family (solute carrier family number 12) are one of the main targets. WNK3 activates the Na(+)-driven cotransporters NCC, NKCC1, and NKCC2 and inhibits the K(+)-driven cotransporters KCC1 to KCC4. WNK4 inhibits the activity of NCC and NKCC1, while in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 56 publications
6
67
0
Order By: Relevance
“…As shown in the present work, L-WNK1 can inhibit the activity of all KCCs, even though only KCC3a and KCC2a isoforms contain a SPAK/OSR1 binding site. We have also previously observed that other WNKs inhibit the KCCs cotransporter that contains no SPAK/OSR1 binding sites (12,19,52). Our data thus suggest that L-WNK1 activates SPAK/OSR1, which in turn phosphorylates KCCs, decreasing their activity.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…As shown in the present work, L-WNK1 can inhibit the activity of all KCCs, even though only KCC3a and KCC2a isoforms contain a SPAK/OSR1 binding site. We have also previously observed that other WNKs inhibit the KCCs cotransporter that contains no SPAK/OSR1 binding sites (12,19,52). Our data thus suggest that L-WNK1 activates SPAK/OSR1, which in turn phosphorylates KCCs, decreasing their activity.…”
Section: Discussionsupporting
confidence: 76%
“…In their study, however, de los Heros et al (11) indicated that SPAK/OSR1 phosphorylates T1048 but may not itself phosphorylate the T991 directly. Regarding S96, which is only present in KCC3a, Melo et al (36) (4,46), and they are able to bypass tonicity requirements for the activation or inhibition of the SLC12 cotransporters (12,19 L-WNK1 is a ubiquitous kinase and its activity is regulated by hypertonicity or hypotonicity. It has been involved in cell volume regulation during changes in osmolality (31,49,68).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lifton and colleagues (54,61,62) propose that the WNK signaling pathway also activates KCCs, including KCC2. WNKs are activated by osmotic stress; however, the upstream signaling remains unknown (38,59,63).…”
Section: Thr-906 and Thr-1007 Mutation In Kcc2 Affects Activity And Smentioning
confidence: 99%